2004
DOI: 10.1111/j.1471-4159.2004.02477.x
|View full text |Cite
|
Sign up to set email alerts
|

A minimal length between tau exon 10 and 11 is required for correct splicing of exon 10

Abstract: Mutations that stimulate exon 10 inclusion into the human tau mRNA cause frontotemporal dementia with parkinsonism, associated with chromosome 17 , and other tauopathies. This suggests that the ratio of exon 10 inclusion to exclusion in adult brain is one of the factors to determine biological functions of the tau protein. To investigate the underlying splicing mechanism and identify potential therapeutic targets for tauopathies, we generated a series of minigene constructs with intron deletions from the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…Although the roles of PSF and SRP20 as splicing factors are well established (Patton et al 1993;Jumaa and Nielsen 1997;Shav-Tal and Zipori 2002;Galiana-Arnoux et al 2003;Sanford et al 2005), not much is known about the function of SRP20 and PSF in neurons. SRP20 regulates splicing of exon 10 of the gene encoding the microtubule-associated protein tau (Yu et al 2004), which might indicate a role for compartmentalized signaling during memory processes. The neuronal expression of Psf is established (Chanas-Sacre et al 1999), but the transcripts it splices in these cells remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the roles of PSF and SRP20 as splicing factors are well established (Patton et al 1993;Jumaa and Nielsen 1997;Shav-Tal and Zipori 2002;Galiana-Arnoux et al 2003;Sanford et al 2005), not much is known about the function of SRP20 and PSF in neurons. SRP20 regulates splicing of exon 10 of the gene encoding the microtubule-associated protein tau (Yu et al 2004), which might indicate a role for compartmentalized signaling during memory processes. The neuronal expression of Psf is established (Chanas-Sacre et al 1999), but the transcripts it splices in these cells remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we demonstrated that the gene encoding the glycosyl phosphatidyl-inositol anchor attachment protein 1 (Gaa1) requires CaMKK␤ for up-regulation by spatial training in males (Mizuno et al 2007). Here, we show that two splicing factors, the splicing factor arginine/serine-rich 3 (Sfrs3/Srp20) (Jumaa and Nielsen 1997;Yu et al 2004) and polypyrimidine tract-binding (PTB) protein-associated splicing factor (Psf) (Chanas-Sacre et al 1999) are differentially expressed in the naïve male hippocampus of CaMKK␤-deficient mice. Since increasing evidence suggests that alternative splicing is an important, but not well understood mechanism of brain plasticity (Bottai et al 2002;Lee and Irizarry 2003;Nijholt et al 2004;O'Connor et al 2004;Rattiner et al 2004;Beffert et al 2005), we studied the expression of Srp20 and Psf in more detail.…”
mentioning
confidence: 99%
“…pCEP4/ SRp55-HA was a gift from Dr. Tarn of the Institute of Biomedical Sciences, Academia Sinica, Taiwan. pCI/SI9-LI10, containing a Tau mini-gene SI9-LI10, comprising Tau exons 9 -11 and part of intron 9 and the full length of intron 10, was described previously (11). Monoclonal antibody against Dyrk1A (8D9) was raised against a histidine-tagged protein containing the first 160 amino acid residues of rat Dyrk1A (18).…”
Section: Methodsmentioning
confidence: 99%
“…SRp55 (serine/arginine-rich protein 55) is a SR protein with an apparent molecular mass of 55 kDa and participates in constitutive and alternative pre-mRNA splicing (6). SRp55 was reported to regulate the alternative splicing of Bim (7), epidermal growth factor (8,9), HIV-1 (10), and Tau (11).…”
mentioning
confidence: 99%
“…The splicing factors SRp20, SRp30c, SRp55, Tra2-b, and 9G8 have all been shown to affect exon 10 splicing. Each of these proteins contains an arginineserine repeat (RS) domain, characteristic of the SR family of splicing factors (Yu et al 2004;Wang et al 2005;Gao et al 2007). SR proteins can act as either alternative splicing enhancers or repressors (Long and Caceres 2009;Shepard and Hertel 2009).…”
Section: Introductionmentioning
confidence: 99%